PENERAPAN SISTEM INFORMASI PROSES PEMBELAJARAN SEBAGAI PENUNJANG FLIPPED CLASSROOM DALAM RANAH KOGNITIF - Kaffah Imanuddin M. R. Santosa; Erik Rahman; Setiawati Setiawati; Frisiska Frisiska (LPPM Unbaja, 2025)
Education is crucial in a civilization because through education humans humanize humans. In Bloom's taxonomy there are three domains that are used as the progress of students, including cognitive, affective, and psychomotor. Technology has developed in the education sector, many learning methods can support students' abilities, especially in the cognitive domain. The emergence of LMS makes it possible to make the learning process more flexible. Given that the teaching resources used are now almost non-physical, it is necessary to integrate the distribution of teaching materials that are easily accessible. Several platforms are competing in perfecting digital-based learning media with the aim of optimizing learning. Pertiwi University uses Sevima Edlink as an LMS for both offline and online learning. The purpose of this research is to find out the optimization of learning by using Edlink in the learning process at Pertiwi University, especially in the Technology Department using descriptive qualitative methods. Edlink is an LMS platform that is engaged in education. Many features support the flipped classroom learning model so that it will support students' cognitive levels quickly. In addition, the virtual class has complete features ranging from attendance, learning materials that are easily integrated into various formats, collection and assessment of assignments, group sharing and interaction in discussions in each session. Thus Edlink LMS can optimize the learning process through flipped classroom learning.